Calibration of Contact Parameters for Moist Bulk of Shotcrete Based on EDEM - Guanguo Ma; Zhenjiao Sun; Hui Ma; Pengcheng Li (Advances in Materials Science and Engineering)
To obtain the contact parameters of the moist bulk of shotcrete accurately and quickly, this study calibrated the contact parameters of the moist bulk of shotcrete by physical stacking test and simulation method. Based on the Hertz–Mindlin with JKR (Johnon–Kendall–Roberts) model, the discrete element simulation is carried out. Using P-BD to screen seven initial parameters, it is found that JKR surface energy, rolling friction coefficient between particles and restitution coefficient of particle impact have significant effects on the angle of repose of the moist bulk of shotcrete. According to B-BD, the second-order regression model of angle of repose and significance parameters was established. Three significant parameters were obtained: JKR surface energy 0.418 J/m2, rolling friction coefficient 0.06 and static friction coefficient 1. The angle of repose obtained by simulation is compared with the physical test value, and the relative error is 1.88%. The results show that the calibration method proposed in this study can accurately simulate the physical stacking test, and can provide a reference for the calibration of contact parameters of the moist bulk of shotcrete.